Transition Economy of Vietnam: A New Horizon of Opportunities - Jurdeczka, Mirosław (Power Shifts in East Asia and Their Implications for Asia–Europe Relations, 2019)
The aim of this article is to present the possibilities for future development of Vietnam’s economy, as it currently represents the model of a transitional economy. In the first section of the chapter the history of economic reforms is presented, as well as the current economic situation. The second part of the article focuses on the National Innovation System as a catalyst for stimulating growth and cooperation enabling a more innovative type of economy. This chapter presents the theoretical role of government-based institutions in bridging between academia and business actors to create a more innovative environment. In the third part of this paper a number of selected threads to the general development of Vietnam’s economy are presented. The final findings highlight the utmost importance of government institutions in developing the right environment within the country for the development of an innovative economy, but also in creating vital connections at international level that are needed for technology and know-how transfer.